Genome‐wide single‐nucleotide polymorphism data reveal cryptic species within cryptic freshwater snail species—The case of the Ancylus fluviatilis species complex. Issue 2 (16th December 2017) - Weiss, Martina; Weigand, Hannah; Weigand, Alexander M.; Leese, Florian
Abstract: DNA barcoding utilizes short standardized DNA sequences to identify species and is increasingly used in biodiversity assessments. The technique has unveiled an unforeseeably high number of morphologically cryptic species. However, if speciation has occurred relatively recently and rapidly, the use of single gene markers, and especially the exclusive use of mitochondrial markers, will presumably fail in delimitating species. Therefore, the true number of biological species might be even higher. One mechanism that can result in rapid speciation is hybridization of different species in combination with polyploidization, that is, allopolyploid speciation. In this study, we analyzed the population genetic structure of the polyploid freshwater snail Ancylus fluviatilis, for which allopolyploidization was postulated as a speciation mechanism. DNA barcoding has already revealed four cryptic species within A. fluviatilis (i.e., A. fluviatilis s. str., Ancylus sp. A–C), but early allozyme data even hint at the presence of additional cryptic lineages in Central Europe. We combined COI sequencing with high‐resolution genome‐wide SNP data (ddRAD data) to analyze the genetic structure of A. fluviatilis populations in a Central German low mountain range (Sauerland). The ddRAD data results indicate the presence of three cryptic species within A. fluviatilis s. str. occurring in sympatry and even syntopy, whereas mitochondrial sequence data only support the existence of one species, with shared haplotypes between species. Our study hence points to the limitations of DNA barcoding when dealing with organismal groups where speciation is assumed to have occurred rapidly, for example, through the process of allopolyploidization. We therefore emphasize that single marker DNA barcoding can underestimate the true species diversity and argue in strong favor of using genome‐wide data for species delimitation in such groups. Abstract : In this study, we detected three more cryptic species within the freshwater snail Ancylus fluviatilis sensu stricto by using genome‐wide SNP data, whereas COI barcoding could only resolve one. Our study therefore shows the limits of DNA barcoding when dealing with cases such as A. fluviatilis, where probably allopolyploidization is involved in the often fast speciation process and highlights the importance to use genome‐wide data in such groups.